An approach to optimal design of composite laminates under elasto-plastic loading conditions - C. A. Conceição António (1997)
A design optimisation process for elasto-plastic material behaviour of laminate composite structures made of thermoplastic resins is described. The approach considers two optimisation levels. At the first level the geometric linear or non-linear behaviour under elasto-plastic loading conditions is considered in order to obtain the optimal solution as a function of ply angles of the plates or shallow shells. At this stage the objective is to recover the plastic zones using only the anisotropic material properties. At the second level the ply thickness of the plates or shallow shells and the height and width of the reinforcement beams are changed to structure weight minimisation under the constraints of maximum allowed displacement or stresses without structural plastic collapse. It is expected that contradictory objectives as minimum elasto-plastic energy and structural weight are satisfied.